A multicentre, randomised, controlled, open-label pilot study on the feasibility of discontinuation of adalimumab in established patients with rheumatoid arthritis in stable clinical remission. Issue 1 (14th January 2016) - Chatzidionysiou, Katerina; Turesson, Carl; Teleman, Annika; Knight, Ann; Lindqvist, Elisabet; Larsson, Per; Cöster, Lars; Forslind, Kristina; van Vollenhoven, Ronald; Heimbürger, Mikael
Abstract : Objectives: Treatment with tumour necrosis factor (TNF) blockers, once started as therapy for rheumatoid arthritis (RA), is usually continued indefinitely. The aim of this trial was to assess the possibility of discontinuing treatment with adalimumab (ADA) while maintaining remission in patients with RA with established disease in stable remission on combination therapy with ADA and methotrexate (MTX). Methods: In a randomised, controlled, open-label pilot study of patients with RA in stable remission treated with ADA+MTX, patients were randomised in a 1:1 ratio to continue with ADA plus MTX (arm AM) or MTX monotherapy (arm M) for 52 weeks. Flare was defined as Disease Activity Score (DAS28) ≥2.6 or a change in DAS28 (ΔDAS28) of >1.2 from baseline at any time. Patients in arm M with a flare restarted ADA. The primary end point was the proportion of patients in remission at week 28. Results: 31 patients were enrolled in the study and randomised to arm AM (n=16) or arm M (n=15). At 28 weeks, 15/16 patients (94%) and 5/15 patients (33%) in arms AM and M, respectively, were in remission (p=0.001). During the first 28 weeks, 50% (8/16) in the AM arm and 80% (12/15) in the M arm had a flare (p=0.08). The number of patients in the AM and M arms with ≥1 ΔDAS28 >1.2 during the first 28 weeks was 1/16 (6%) and 8/15 (53%), respectively (p=0.005). Conclusions: In this study, remission was rarely maintained in patients with long-standing disease who discontinued ADA. Discontinuation may be feasible in only a minority of patients with established RA in stable clinical remission. Trial registration number: NCT00808509.